A Framework for Predictive Modeling in Sustainable Projects - Labban, Tarek (2012)
A Master of Science thesis in Engineering Systems Management, Construction Management Theme by Tarek Labban entitled, "A Framework for Predictive Modeling in Sustainable Projects," submitted in May 2012. Thesis advisor is Dr. Salwa Beheiry and thesis co-advisor is Dr. Ghassan Abu-Lebdeh. Available are both soft and hard copies of the thesis.